Retiring From Pediatric Emergency Medicine Too Soon?: A Survey to Discover the Reasons and Start a Conversation About Solutions. Issue 6 (14th June 2022) - Bansal, Bharati Beatrix; Mathew, Matthew Sunil; Booker-Nubie, Quiera; Messiah, Sarah E.; Wang, Vincent J.
Abstract : Objective: Pediatric emergency medicine is a subspecialty known for high acuity, high stress, and variable scheduling that may be difficult to maintain as one gets older. This survey sought to gain information on the reasons or plans for early retirement in pediatric emergency medicine and offer ways to address these concerns to improve longevity in the field. Methods: A cross-sectional survey was sent via email to board-certified pediatric emergency medicine physicians who were older than 50 years to assess preretirement and postretirement considerations. Results were collected from October 3, 2019, through March 15, 2020. Results: Pediatric emergency medicine physicians who find it more difficult to perform simple procedures are 3.02 (1.23–7.36) times more likely to retire before the age of 66 years. In addition, women were significantly more likely to report an intention to retire before the age of 66 years versus men (50% vs 31%, P = 0.022). Discussion: The topic of retirement in a field that requires a wide range of procedural skills as well as constantly evolving technology is important. Understanding when and why physicians choose to retire may identify strategies to make it possible for pediatric emergency medicine physicians to prolong their careers. This may involve changes in work hours, a shift in responsibilities to a greater educational or mentor role, and/or providing opportunities to maintain skills. Conclusions: Perceived basic procedure skills deterioration significantly increased the risk for early retirement. In addition, women were significantly more likely to express intention to retire before the age of 66 years. Further research should be directed toward obtaining more detailed information to develop strategies to retain pediatric emergency medicine physicians in a capacity that benefits the physician, their institution, and their patients.